Antimicrobial Effect of a Proteolytic Enzyme From the Fruits of Solanum granuloso-leprosum (Dunal) Against Helicobacter pylori - Salinas Ibáñez, Ángel Gabriel; Vallés, Diego; Adaro, Mauricio; Barberis, Sonia; Vega, Alba E. (Frontiers in Nutrition, 2021)
Helicobacter pylori is a Gram negative, helix-shaped and microaerophilic bacteria that colonizes the human gastric mucosa, causing chronic infections, gastritis, peptic ulcer, lymphomas associated with lymphoid mucosa tissue, and gastric cancer. H. pylori is considered as Type 1 human carcinogen by WHO. The prevalence of H. pylori infection is estimated in more than half of the world population. Treatment of H. pylori infection includes antibiotics and proton pump inhibitors, but the increasing antibiotic resistance promotes the research of novel, more effective and natural antibacterial compounds. The aim of this work was to study the effect of the partially purified proteolytic extract (granulosain) from the fruits of Solanum granuloso-leprosum (Dunal), a South American native plant, against Helicobacter pylori; in order to obtain a natural food additive or ingredient for the production of anti-H. pylori functional foods. Furthermore, granulosain could also be used as a natural adjunct to conventional therapies. Granulosain antibacterial activity was evaluated as minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against H. pylori NCTC 11638 (reference strain) and four H. pylori wild strains; using a micro dilution plating technique (Clinical and Laboratory Standards Institute). All the strains tested were susceptible to granulosain with MIC and MBC values of 312.5  0.01 µg/mL. The effect of granulosain on the transcription of H. pylori virulence genes: omp18, ureA and flaA, with respect to a housekeeping gene (16S rRNA), was evaluated by RT-PCR technique. The band intensity between virulence and control genes was correlated under treated/untreated conditions, using the ImageJ program. Granulosain significantly decreased the expression of the omp18, ureA, flaA genes (p < 0.05). Finally, the combined inhibitory effect of granulosain and a conventional antibiotic, such as: amoxicillin (AML, 10 g), clarithromycin (CLA, 15 g), levofloxacin (LEV, 5 g) or metronidazole (MTZ, 5 g) was evaluated, using the agar diffusion technique. Granulosain showed significant synergistic effect on AML, CLA and LEV, but none effect on MTZ. These pioneering results indicate that granulosain, could be used as natural food additive for the production of anti-H. pylori functional foods and as natural adjuvant compound for conventional therapies against H. pylori strains.